Examining lecturers' questions and level of reflection during post-simulation debriefing in Malawi: A qualitative study - Charity Kabondo; Ursula Kafulafula; Lily Kumbani; Christina Furskog-Risa; Ingrid Tjoflåt (Elsevier, 2024)
Background: Simulation-based education has recently been promoted among midwifery students in Malawi. Reflective debriefing is essential for a successful educative simulation. It is therefore crucial to explore debriefing practice, particularly when simulation-based education is novel. Therefore, the study aimed to explore practice of debriefing with focus on level of reflection in questions posed by lecturers and responses from midwifery students when learning postpartum haemorrhage. Methods: The study applied qualitative exploratory design. During debriefing of a simulation session on postpartum hemorrhage management, data were collected through audio recordings. Seven midwifery lecturers and 107 midwifery students from midwifery education program in Malawi participated in the study. Using Gibbs's reflective cycle, data from the lecturers' questions and midwifery students' responses were analysed by rating stages of reflection. The reporting of the results follows Consolidated Criteria for Reporting Qualitative Research. Results: Most of lecturers' questions and midwifery students' responses were evaluative, 46% and 47%, respectively. The fewest questions and responses were conclusive, 4% and 2% respectively. Only 12% of the lecturers' questions were analytic, while 16% of students' responses were rated as analytic. Conclusion: The results revealed that debriefing provides a forum for students to reflect on their simulated experience. Though, more evaluative questions and responses were elicited from lecturers and students, respectively, than the rest of the stages in Gibbs's reflective cycle. If debriefing in simulation-based education is going to pave the way for student reflection in Malawi, it is necessary to enhance debriefing practices through further training.